The Influence of Good Corporate Governance, Non Performing Financing, Capital Adequacy Ratio, Financing to Deposit Ratio on Financial Performance (Case Study of Sharia Banks in Indonesia for the period 2018 – 2022) - Wulandari, Dwi Siva (Universitas Mercu Buana, 2024)
This research aims to determine and analyze the influence of Good Corporate Governance, Non Performing Financing, Capital Adequacy Ratio, and Financing to Deposit Ratio on Return on Assets of Sharia Banks in Indonesia in 2018 - 2022. The population in this research is 13 Sharia Commercial Banks in Indonesia. Indonesia for the period 2018 – 2022. The sample used was 10 Sharia Commercial Banks. The data collection method uses the documentation method. The data analysis method in this research uses the Eviews program application. The results of this research are that Good Corporate Governance has no effect on Return On Assets, Non Performing Financing has a negative effect on Return On Assets, Capital Adequacy Ratio has no positive effect on Return On Assets and Financing to Deposit Ratio has no positive effect on Return On Assets.